Interpretation of the Application of Law in Islamic Families in Indonesia - Sahara, Elfi; Mulyani, Ridha (Samara: Journal of Islamic Law and Family Studies, 2025)
In Indonesia's legal system, which is a state based on law (rechstaat), positive law is enforced, namely the law that applies in a certain place at a certain time as a valid legal system. The type of research used is library research, which involves the use of written materials such as manuscripts, books, magazines, newspapers, and other documents containing information about inheritance and gift laws currently in force in Indonesia, both according to Islamic law and Indonesian civil law. The nature of the research in this article is descriptive-analytical, which is research that aims to describe in detail the characteristics or features of a developing or ongoing situation as an influence in producing legal products in accordance with the developments of the times and places, which in this case will attempt to explain the importance of legal interpretation of legislation to produce fair and beneficial laws. The relationship between law and society is reciprocal; sometimes law influences society, and vice versa, society influences law. However, due to the value of legal certainty in a fixed rule that has been codified in the form of legislation, the law is sometimes understood in a static and rigid manner, thereby failing to provide justice and benefit in certain cases.  Thus, it can be said that the method of interpretation is one of several methods for discovering laws that have value in terms of justice and benefit, especially methods that must be mastered by judges in court proceedings, including grammatical, historical, systematic, extensive, restrictive, valid, teleological, interdisciplinary, multidisciplinary, comparative, and futuristic interpretations. In terms of relevance, legal interpretation methods are highly significant for the development of law characterized by certainty, justice, and public welfare, such as in the fields of Islamic family law and Islamic economics.